A survey of graduates’ perceptions on a Chinese medical school’s traditional and reform curricula - Sherer, Renslow (Perspect Med Educ, 2016)
A medical school in China engaged in reform in 2009 by adapting the medical curriculum of the University of Chicago, USA. Freshmen volunteered for the reform and 50 were randomly selected while the rest remained in the traditional curriculum. In 2014 a study was conducted to determine whether the views of traditional and reform curriculum students on their respective educational experience differed and to identify reform areas that needed improvement. A survey was administered to graduating students to gauge their views on basic science and clinical science education, clerkships, general medical education, and readiness for residency training. Frequency distributions, Mann-Whitney U tests, and Chi-squared tests were used for analysis. Reform curriculum students were more positive about their basic science and clinical science instruction. Clerkships were only somewhat satisfactory to students in both curricula. Reform curriculum students were more likely than those following the traditional curriculum to consider instruction in clinical decision-making and patient care as ‘adequate’. Instruction in population health was considered inadequate by the majority of students. Reform curriculum students were more confident about their preparedness for residency. The traditional curriculum was in need of reform. Reform has been effectively implemented and has increased student confidence and satisfaction with their education although there is room for improvement.